Extraction and Determination of Copper(II) from Wastewater with Hydrophilic Ionic Liquid-Salt Aqueous Two-Phase System - Sha, Ou; Zhou, Yun; Ma, Wei-Xing (Asian Journal of Chemistry, 2011)
In this paper, a novel method of extraction and spectrophotometric determination of copper in ionic liquid aqueous two-phase system(ATPS) formed by a hydropilic ionic liquid 1-ethyl-3- methylimidazolium ethyl sulfate [C2mim][ESO4] and K2HPO4 was developed. In the ionic 1iquid aqueous two-phase system of pH 8, the complex formed by acid chromium blue K and Cu2+ had a high absorbance with the maximum absorption of 541 nm. The effects of ionic liquid dosage, solution acidity, the dosages of acid chromium blue K and salt on the extraction determination of copper were studied. Beer’s law was obeyed in the range of 0.040-2.0 μg/mL Cu2+. The method has been applied to the determination of copper in electroplating wastewater and standard copper sample GBW(E)08036.